Analisis Strategi dalam Meningkatkan Keunggulan Bersaing pada UMKM Teh Sila di Masa Pandemi Covid-19 - Pertiwi, Friza; Dewi Anggraeni, Nanda; Dwie Nur Rizki, Ilham; Andriyana, Rantika; Frandiawan, Dega (PUBLICNESS: Journal of Public Administration Studies, 2023)
The purpose of this research is to find out the right strategy needed by UKM Teh Sila to identify the strengths, weaknesses, opportunities and threats they face. This study used a qualitative approach with qualitative data from interviews and observations. Data analysis techniques in this study were processed using the IFE Matrix, EFE Matrix, and SWOT Matrix. The results of this study indicate that Teh Sila SMEs need several strategies that can increase their competitive advantage during a pandemic through two categories of strategies, namely general strategies and new strategies that can be implemented during the COVID-19 pandemic.